IMPLEMENTATION OF THE VILLAGE FUND PROGRAM IN DEVELOPMENT AND COMMUNITY EMPOWERMENT IN LENGKONG DISTRICT SUKABUMI REGENCY - Qinanti Maulid NP; Ike Rachmawati; Rizki Hegia Sampurna (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
Village funds are a means to support the implementation of community empowerment, Development, and village government in improving community welfare. This research aims to find out how the implementation of the Village Fund Program in Development and Community Empowerment is carried out in the Lengkong District. This research method uses a qualitative research method with a descriptive approach using the theory from Charles O. Jones. The technique used in determining informants is a non-probability sampling techniques with snowball sampling. Data collection techniques include observation, interviews, documentation, and audio-visual materials. The results of this study indicate that the Implementation of the Village Fund Program in Development and Community Empowerment in Lengkong District has been running well, judging from the organization, parties involved, implementation activities, and operational procedures that have been running well. Communication and coordination between the parties involved are going well, and from the application of human resources is still not evenly distributed; public response is also pro and contra. Meanwhile, the efforts made have been going well, and the implementation of development and community empowerment is in accordance with the available budget.